2018
DOI: 10.1017/jfm.2018.751
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and acceleration statistics in rapidly rotating Rayleigh–Bénard convection

Abstract: Background rotation causes different flow structures and heat transfer efficiencies in Rayleigh–Bénard convection (RBC). Three main regimes are known: rotation-unaffected, rotation-affected and rotation-dominated. It has been shown that the transition between rotation-unaffected and rotation-affected regimes is driven by the boundary layers. However, the physics behind the transition between rotation-affected and rotation-dominated regimes are still unresolved. In this study, we employ the experimentally obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 76 publications
(131 reference statements)
2
15
1
Order By: Relevance
“…Moving down in Ro (or E) to the rotation-dominated range at Ro ≈ 0.1, Re is rapidly reduced. These results have been confirmed by Rajaei et al [99] using PTV, identifying the ratio Re hor /Re ver , i.e. the ratio of horizontal over vertical velocity fluctuations, as a good indicator of entering the rotation-dominated columnar range.…”
Section: Convection In Watersupporting
confidence: 75%
See 2 more Smart Citations
“…Moving down in Ro (or E) to the rotation-dominated range at Ro ≈ 0.1, Re is rapidly reduced. These results have been confirmed by Rajaei et al [99] using PTV, identifying the ratio Re hor /Re ver , i.e. the ratio of horizontal over vertical velocity fluctuations, as a good indicator of entering the rotation-dominated columnar range.…”
Section: Convection In Watersupporting
confidence: 75%
“…At the same time, the trick is to still be able to reliably provide Rayleigh numbers small enough to explore the rotation-dominated range; no simple task given that Ra ∼ H 3 [86]. That is [32,95]; King et al [94,96]; Niemela et al [38]; Weiss and Ahlers [46,97]; Cheng et al [40]; Cheng et al [44]; Lu et al [90]; Kunnen et al [33,45,98]; Rajaei et al [71]; Rajaei et al [99]; Shi et al [73]; Stevens et al [100]; Horn and Shishkina [101]; de Wit et al [87]; Yang et al [29] and Weiss et al [51].…”
Section: Convection In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…square cuboid or cylinder) as well as by choice of boundary condition (no-slip or stress-free; zero-heat-flux or constant temperature). In contrast, experiments must resort to lateral confinement, where an upright cylinder is by far the most popular geometry [14][15][16][17][18][19]. In that case a parameter describing the geometry is required, for example the diameter-to-height aspect ratio Γ = D/H.…”
Section: Introductionmentioning
confidence: 99%
“…Even if our setup is completely different we can make a parallel with two new studies about 3D rotating Rayleigh-Bénard Convection. Rajaei et al [31] recently published new results about the rotation dominated regime in rapidly rotating Rayleigh-Bénard convection. They found that the transition to the rotation dominated regime coincides with the suppression of vertical motions, the strong penetration of vortical plumes into the bulk and a reduced interaction of vortical plumes with their surroundings.…”
Section: Convective Heat Fluxmentioning
confidence: 99%